Demographic, clinical and laboratory differences between paediatric acute COVID-19 and PIMS-TS—results from a single centre study in the UK - Jiju, Prince; Matalliotakis, Michail; Lane, Steven; Wong, Waison; Hedrich, Christian M.; Pain, Clare E. (Frontiers in Pediatrics, 2023)
Background: Paediatric symptomatic SARS-CoV-2 infections associate with two presentations, acute COVID-19 and paediatric inflammatory multisystem syndrome temporally associated with SARS-CoV-2 (PIMS-TS). Phenotypic comparisons, and reports on predictive markers for disease courses are sparse and preliminary. Methods: A chart review of COVID-19 and PIMS-TS patients (≤19 years) admitted to Alder Hey Children's NHS Foundation Trust, a tertiary centre in the North-West of England, was performed (02/2020-09/2022). Results: A total of 161 symptomatic COVID-19 and 50 PIMS-TS patients were included. Peaks in admissions of patients with PIMS-TS occurred approximately 4 weeks after those for acute COVID-19. The incidence of in-patients with PIMS-TS reduced over time, and there were no admissions after February 2022. When compared to acute COVID-19, PIMS-TS patients were older (median: 10.3 years versus 2.03 years; p<0.001). There were no differences in gender distribution, but minority ethnicities were over-represented among PIMS-TS patients. Regional ethnic distribution was reflected among acute COVID-19 patients (66% versus 84.5% White Caucasian, p=0.01). Pre-existing comorbidities were more common among acute COVID-19 patients (54.7% versus 8%, p<0.001). PIMS-TS patients more commonly presented with abdominal symptoms (92% versus 50.3%), neurological symptoms (28% versus 10.6%) and skin rashes (72% versus 16.8%), (p≤0.01) when compared with acute COVID-19, where respiratory symptoms were more common (51.6% vs 32%, p=0.016). PIMS-TS more frequently required intensive care admission (64% versus 16.8%), and inotropic support (64% versus 9.3%) (all p<0.05). More deaths occurred among acute COVID-19 patients (0 versus 7 (4.4%)), with 5/7 (71%) in the context of pre-existing comorbidities. When compared to acute COVID-19, PIMS-TS patients exhibited more lymphopenia and thrombocytopenia, a more pronounced acute phase reaction, and more hyponatraemia (p<0.05). Partial least square discriminant analysis of routine laboratory parameters allowed (incomplete) separation of patients at diagnosis, and variable importance projection (VIP) scoring revealed elevated CRP and low platelets as the most discriminatory parameters. Conclusion: Admissions for PIMS-TS reduced with increasing seroconversion rates in the region. Young age and pre-existing comorbidities associate with hospital admission for acute COVID-19. While PIMS-TS may present more acutely with increased need for intensive care, acute COVID-19 had an increased risk of mortality in this cohort. patients included.